2002
DOI: 10.1577/1548-8675(2002)022<0870:sccwth>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Sampling Channel Catfish with Tandem Hoop Nets in Small Impoundments

Abstract: Because populations of channel catfish Ictalurus punctatus have been difficult to sample in small impoundments, we determined whether tandem hoop net series (three nets tied in series and baited with cheese) fished for 3 d could effectively sample these populations. In 2000 we compared seasonal catch rates (catch per unit effort (CPUE), defined as the number of fish caught per series) and length frequencies (total length (TL); mm) of channel catfish captured with two types of tandem series (long versus short b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
86
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(90 citation statements)
references
References 13 publications
4
86
0
Order By: Relevance
“…Number of samples (effort) needed to achieve two estimates of sampling precision (relative standard error (RSE)) at two levels of confidence is given. lakes sensu Michaletz & Sullivan 2002), trotlines baited with Zote TM soap appears to be a viable option for sampling channel catfish and this could be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Number of samples (effort) needed to achieve two estimates of sampling precision (relative standard error (RSE)) at two levels of confidence is given. lakes sensu Michaletz & Sullivan 2002), trotlines baited with Zote TM soap appears to be a viable option for sampling channel catfish and this could be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Tandem hoop nets have been gaining popularity as a means to sample channel catfish Ictalurus punctatus in reservoirs (Michaletz & Sullivan 2002;Bodine et al 2013) but it is often associated with high bycatch, particularly aquatic turtles (order Testudines). Few studies have quantified bycatch of turtles but personal experience and anecdotal evidence from other biologists have confirmed that this is an issue.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the study of freshwater bycatch lags far behind that of marine bycatch (Soykan and others 2008; Raby and others 2011), freshwater turtle bycatch mortality has been documented in inland commercial fisheries where passive fishing gears such as hoop, fyke, and trap nets are used (Michaletz and Sullivan 2002;Horne and others 2003;Barko and others 2004;Carrière 2007;Larocque and others 2012a). Delayed maturity, high juvenile mortality, and low adult mortality are life-history characteristics that make turtles particularly susceptible to population declines, especially in response to small increases in adult mortality (Brooks and others 1990;others 1993, 1994;Gibbs and Shriver 2002;Bulté and others 2010).…”
Section: Introductionmentioning
confidence: 99%